2015
DOI: 10.1038/jid.2015.231
|View full text |Cite
|
Sign up to set email alerts
|

CCN1, a Pro-Inflammatory Factor, Aggravates Psoriasis Skin Lesions by Promoting Keratinocyte Activation

Abstract: Psoriasis is a common chronic skin disease characterized by epidermal hyperplasia and inflammation. The pathogenesis of psoriasis is multifactorial and is not fully understood. Here we demonstrate that CCN1 (also called Cyr61, which is short for cysteine-rich 61), an extracellular matrix protein that is also considered a pro-inflammatory factor, is highly expressed in the lesional skin of psoriasis patients, as well as in that of imiquimod (IMQ)- and IL-23-treated psoriasis-like mice. Then we show that blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
65
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 36 publications
13
65
1
Order By: Relevance
“…In our previous study, we found that CCN1 was highly expressed in the lesional skins of psoriasis patients and was involved in the pathogenesis of psoriasis by promoting keratinocyte activation27. As CCN1 is considered as a pro-inflammatory factor in RA pathology, we further explored whether CCN1 contributed to the inflammation of psoriasis.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In our previous study, we found that CCN1 was highly expressed in the lesional skins of psoriasis patients and was involved in the pathogenesis of psoriasis by promoting keratinocyte activation27. As CCN1 is considered as a pro-inflammatory factor in RA pathology, we further explored whether CCN1 contributed to the inflammation of psoriasis.…”
Section: Resultsmentioning
confidence: 97%
“…In our previous report, we demonstrated that CCN1 promoted KC activation through the integrin receptor α6β127. To determine whether CCN1 stimulated IL-1β expression by binding to α6β1, we silenced α6β1 production by siRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice received intraperitoneal injections of 200 μg/day of either anti-Cyr61 mAb 093G9 or control IgG1 (Millipore, Billerica, MA, USA) 2 days after IMQ treatment. After16 days later mice were sacrificed and skin samples were collected and inspected [4].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%